Climate change as a polarizing cue: Framing effects on public support for low-carbon energy policies. (July 2018) - Feldman, Lauren; Hart, P. Sol
Highlights: We evaluate how framing affects support for four low-carbon energy policies among U.S. partisans. For Republicans, a climate change frame lowers support relative to pollution or security frames. We find framing effects for renewable energy, carbon tax, and fuel efficiency policies, but not nuclear power. No framing effects are observed among Democrats or Independents. Results support a motivated reasoning rather than heuristic processing mechanism. Abstract: This study examines how public support for four specific low-carbon energy policies (renewable energy investment, revenue-neutral carbon tax, fuel efficiency regulations, expansion of nuclear power) varies when these policies are framed as a way to reduce either climate change, air pollution, or energy dependence. A survey question wording experiment with a nationally representative U.S. sample is utilized. We find framing effects only among Republicans, whose policy support was lower in response to the climate change frame versus the air pollution and energy security frames for all policies except nuclear power. This suggests that framing effects are conditional on political partisanship and policy content. When testing the processing mechanism behind these effects, we find no evidence that the climate change frame functions as a simple heuristic; rather, the findings are consistent with motivated reasoning, whereby the framing effects on policy support are mediated by the policy's perceived relative benefits and costs.